Does Education Influence Self Care Management in Diabetes Mellitus Patients? : Systematic Review - Nadatien, Ima; Puspita, Uci Nurhayati; Kartini, Yanis; Setiyowati, Eppy; Hidayah, Nur (Journal of Applied Nursing and Health, 2024)
Background: Diabetes mellitus is a major health problem in society. Indonesia ranks 7th out of 10 countries—metabolic disorders in the body cause diabetes. Several factors also influence the occurrence of diabetes mellitus, including genetic factors, age, and lifestyle (eating patterns and daily activities). This research aims to determine the effect of health education on self-care management in type 2 diabetes mellitus patients. Methods: The method used in this research is a systematic review with systematic reviews (PRISMA) using several journal databases from Google Scholar, Science Direct, and Pubmed. from 2020-2024 with the keywords " Diabetes mellitus, "" health education," or " self-care management." Articles that are ready to be reviewed are ten articles obtained using PRISMA. Results: The results of a systematic review study show that providing diabetes self-management education has an influence on self-care management in patients with type 2 diabetes mellitus. Conclusion: It is hoped that the presence of diabetes self-management education will increase knowledge and change the individual's mindset so that they can care. themselves and prevent complications and will improve their quality of life